An Enterprise Resource Planning System Solution for Small-Mid Size Enterprises: An Information System Development Case Study - Ashari Imamuddin (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
The paper aims to present a solution of managing an enterprise information system or enterprise resource planning (ERP) in small-mid size enterprises (SMEs). The research was focused on developing an integrated enterprise information system for resolving faced problems in managing SMEs’ business. The methods were investigating business requirements regarding information system, system analysis, system design which included processes, data, and interface model, implementation of system design using selected programming language, and system testing which included unit and integrated testing. The research produced a tested model of the enterprise information system and a working enterprise resource planning information system software named Qinova ERP. The system is implemented in a real environment, a hazardous waste transporter company in Indonesia, and the system has been tackling their business information system management problems. The system is ready to be employed to the different companies in the same industry with minor revision and to the other industries with some customizations to adapt their business requirements.